MOMENTOS DE LOS LÍMITES GEOMÉTRICOS Y SU APLICACIÓN AL CONTROL DE CALIDAD AUTOMATIZADO EN LA INDUSTRIA - Montenegro Joo, Javier (2006)
In this research the performance of the Chen's Improved (Boundary) Moments is carefully compared to that of the traditional (Massive) Moments. To achieve this investigation, the pattern recognition power of the former is thoroughly assessed against that of the latter. The boundary moments are evaluated by two methods, in the first by edge-tracing, in the second method the edge pixels are considered as though they are met when sweeping the image space. It is concluded that the computation of the Boundary Moments by sweeping the image space associates minimum computational complexity to a high enough object classification efficiency, thus they may be used in lieu of the traditional moments.